Respuesta :

Proved Below

[tex]\Longrightarrow x-y = \sqrt{(x+y)^2-4xy}[/tex]

[tex]\Longrightarrow x-y = \sqrt{x^2+2(x)(y)+ y^2-4xy}[/tex]

[tex]\Longrightarrow x-y = \sqrt{x^2+2xy-4xy+y^2}[/tex]

[tex]\Longrightarrow x-y = \sqrt{x^2-2xy+y^2}[/tex]

[tex]\Longrightarrow x-y = \sqrt{(x-y)^2}[/tex]

[tex]\Longrightarrow x-y =x-y[/tex]

Let's check

x-y=√(x+y)²-4xy

Solve RHS

  • √(x+y)²-4xy
  • √x²+2xy+y²-4xy
  • √x²+y²-2xy
  • √(x-y)²
  • x-y

Hence proved

ACCESS MORE
EDU ACCESS
Universidad de Mexico